High-temperature-resistant low-permeability CPVC chemical pipe and preparation process thereof
By adding sodium carboxymethyl cellulose quaternary ammonium salt modified boron nitride nanosheets and adenine metal complex heat stabilizers to CPVC pipes, and combining p-phenylenediamine and terephthaloyl chloride to generate aramid nanomaterials, the problems of easy degradation and media permeation of CPVC pipes at high temperatures are solved, achieving the effect of high temperature resistance and low permeability.
Patent Information
- Application Number
- CN202511234344.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2025-12-05
AI Technical Summary
In the existing technology, CPVC pipes have shortcomings in high temperature resistance and impermeability, resulting in short service life and high maintenance costs under harsh working conditions.
By adding sodium carboxymethyl cellulose quaternary salt modified boron nitride nanosheets and adenine metal complex heat stabilizers, and utilizing their high thermal conductivity and barrier properties, aramid nanomaterials are generated by in-situ polymerization of p-phenylenediamine and terephthaloyl chloride, forming a labyrinthine barrier structure to inhibit high-temperature degradation of CPVC and media penetration.
This improves the high-temperature resistance and impermeability of CPVC pipes, extends their service life, and reduces maintenance costs.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of CPVC, in particular to a high-temperature-resistant and low-permeability CPVC chemical pipe and a preparation process thereof. BACKGROUND
[0002] Chlorinated polyvinyl chloride (CPVC) pipe has excellent chemical corrosion resistance, mechanical strength and forming processability, and is widely used in the fields of chemical industry, petrochemical industry, industrial water treatment and the like to transport corrosive media such as hydrochloric acid, sulfuric acid and organic solvents. However, with the development of industrial production conditions towards high temperature and high concentration, the performance of the existing CPVC pipe has been difficult to meet the actual use requirements, and there are obvious technical shortcomings.
[0003] In terms of high-temperature resistance, the traditional CPVC pipe has a low Vicat softening temperature, and is prone to molecular chain thermal creep in a high-temperature environment for a long time, resulting in an excessive longitudinal shrinkage rate of the pipe and even structural rupture. Meanwhile, the commonly used thermal stabilizers or heavy metal-containing (such as lead salt) stabilizers do not meet the environmental protection requirements, or are prone to zinc burning (such as ordinary zinc-based stabilizers), and cannot continuously inhibit the high-temperature degradation of CPVC, further exacerbating the insufficient high-temperature resistance of the pipe.
[0004] In terms of permeation resistance, the CPVC matrix itself has microvoids, forming a medium permeation channel. When transporting strong corrosive or volatile media, the medium is prone to permeation, which not only accelerates the aging of the inner wall of the pipe and shortens the service life, but also may cause environmental pollution and even safety hazards. In previous improvement schemes, the single addition of inorganic fillers is prone to agglomeration due to poor compatibility with the matrix, and the blocking effect is limited. Although the multi-layer composite pipe can improve the blocking property, it has the defects of complex processing technology, high cost and weak interlayer bonding force and easy delamination.
[0005] In summary, the existing CPVC chemical pipe has the defects of insufficient high-temperature stability and resistance to medium permeation, resulting in a short service life and high maintenance cost under severe working conditions, and it is urgent to develop a CPVC chemical pipe with excellent high-temperature resistance, low permeability and simple process and a preparation process thereof. SUMMARY
[0006] The application aims to provide a high-temperature-resistant and low-permeability CPVC chemical pipe and a preparation process thereof to solve the problems in the prior art.
[0007] To achieve the above-mentioned purpose, the application provides the following technical scheme. The application discloses a preparation process of high-temperature-resistant and low-permeability CPVC chemical pipe material. S2: the premix is added into a double-screw extruder, calcium stearate is added, melt blending is carried out, extrusion molding is carried out, vacuum shaping is carried out at room temperature, and cooling shaping is carried out, so that the high-temperature-resistant and low-permeability CPVC chemical pipe material is obtained. Further, the heat stabilizer is composed of adenine metal complex and theophylline.
[0008] Further, the preparation method of the quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet comprises the following steps: step (1): oleamide propyl dimethylamine, concentrated hydrochloric acid and ethanol are added into a reaction container, stirring is carried out at room temperature for 10-15 min, epichlorohydrin is added, heating is carried out to 60-65 DEG C, and reaction is carried out for 2-2.5 h; 60-62 DEG C is rotated and evaporated; excessive ethyl acetate is added into the crude product, freezing recrystallization is carried out, supernatant is removed, ethyl acetate is added again, and the freezing recrystallization is repeated for three times, so that the quaternary ammonium salt intermediate is obtained. Step (2): the carboxymethyl cellulose sodium is ultrasonically dispersed in N,N-dimethylformamide, sodium hydroxide solution is added, stirring is carried out for 10-15 min, the quaternary ammonium salt intermediate is added, heating is carried out to 80-85 DEG C, and reaction is carried out for 5-5.5 h; cooling is carried out to room temperature, the upper solvent is removed, excessive ethyl acetate is added, stirring is carried out, standing is carried out, the upper supernatant is removed, the above-mentioned operation of adding ethyl acetate, stirring and standing is repeated for three times, and rotary evaporation is carried out, so that the quaternary ammonium salt carboxymethyl cellulose sodium is obtained. Step (3): the quaternary ammonium salt carboxymethyl cellulose sodium and the boron nitride nanosheet are added into a ball milling tank, ball milling is carried out for 10-12 h in a nitrogen atmosphere, deionized water is added, ultrasonic dispersion is carried out, centrifugal operation is carried out, and vacuum drying is carried out, so that the quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet is obtained.
[0009] Further, in the preparation process of the quaternary ammonium salt intermediate, the molar ratio of the oleamide propyl dimethylamine to the epichlorohydrin is 1:(1-1.5).
[0010] Further, in the preparation process of the quaternary ammonium salt carboxymethyl cellulose sodium, the mass ratio of the carboxymethyl cellulose sodium to the quaternary ammonium salt intermediate is 9:(1.6-2.0).
[0011] Further, in the preparation process of the quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet, the mass ratio of the quaternary ammonium salt carboxymethyl cellulose sodium to the boron nitride nanosheet is (4-5):1.
[0012] Further, in the heat stabilizer, the mass ratio of the adenine metal complex: theophylline is (2-3):(1-1.5).
[0013] Further, the preparation process of the adenine metal complex comprises the following steps: adding adenine and potassium hydroxide into deionized water, heating to 100-105 DEG C and stirring uniformly, adding anhydrous zinc acetate, keeping reaction for 2-2.5 h, cooling, filtering, washing the precipitate, vacuum drying, grinding, and obtaining the adenine metal complex.
[0014] Further, in the preparation process of the adenine metal complex, the mass ratio of adenine: potassium hydroxide: anhydrous zinc acetate is (1.35-1.5):(0.5-0.52):(1.84-1.96).
[0015] Further, the proportion of each component in the premix is as follows in terms of mass fraction: 90-100 parts of chlorinated polyethylene powder, 12-20 parts of quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet, 4-6 parts of heat stabilizer, 2-4 parts of p-phenylenediamine and 4-8 parts of terephthaloyl chloride; and in the preparation process of the high-temperature-resistant and low-permeability CPVC chemical pipe, the addition amount of calcium stearate is 0.2-0.5% of the mass of the premix.
[0016] Compared with the prior art, the present application has the following beneficial effects: 1. The quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet is added in the present application, and the high thermal conductivity of the quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet can quickly conduct the heat of hot spots to the whole pipe, reduce the local temperature difference, avoid the CPVC molecular chain rupture caused by local overheating, and the radially arranged quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet not only acts as a barrier layer, but also can be used as a rigid filler to inhibit the high-temperature creep of the CPVC molecular chain; at the same time, the C=C bond of the oil on the surface of the quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet can further adsorb the HCl released by the high-temperature degradation of CPVC in an acidic environment, thereby inhibiting the "zipper degradation" of CPVC caused by the catalysis of HCl from the source; the adenine metal complex acts as a main stabilizer, combines with the active Cl of CPVC, and adsorbs HCl, thereby inhibiting degradation; theophylline forms a coordination effect with the adenine metal complex, and wraps the generated ZnCl2, thereby avoiding the "zinc burning" problem of traditional zinc-based stabilizers, and greatly improving the high-temperature resistance of the CPVC pipe. 2+ The adenine metal complex acts as a main stabilizer, combines with the active Cl of CPVC, and adsorbs HCl, thereby inhibiting degradation; theophylline forms a coordination effect with the adenine metal complex, and wraps the generated ZnCl2, thereby avoiding the "zinc burning" problem of traditional zinc-based stabilizers, and greatly improving the high-temperature resistance of the CPVC pipe.
[0017] 2、The aramid nanomaterial is generated by in-situ polymerization of p-phenylenediamine and p-phenylenediamine dichloride in the CPVC matrix, the aramid nanomaterial and the molecular chain of CPVC form strong hydrogen bond effect, fill the microvoids in the CPVC matrix, reduce the medium penetration channel, meanwhile, the aramid nanomaterial synthesized in-situ is uniformly dispersed in the CPVC matrix without agglomeration problem; the quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet is arranged in parallel along the radial direction of the pipe material, forming a "labyrinth barrier structure", and the penetration path of the corrosion medium is greatly prolonged through the interlayer gap of the layered filler, thereby improving the anti-permeation performance. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.
[0019] Embodiment 1: A preparation process of a high-temperature-resistant and low-permeation CPVC chemical pipe, comprising the following steps: S1: 1.35 g of adenine, 0.5 g of potassium hydroxide are added into 100 mL of ionized water, and stirred uniformly after being heated to 100 DEG C, 1.84 g of anhydrous zinc acetate is added, and the reaction is kept for 2 h, then cooled, filtered, the precipitate is washed, vacuum dried, ground, and an adenine metal complex is obtained; S2: 4 g of the adenine metal complex and 2 g of theophylline are compounded to obtain a thermal stabilizer; S3: 1 mmol of oleamide propyl dimethylamine, 0.01 mmol of concentrated hydrochloric acid, and 50 mL of ethanol are added into a reaction container, stirred at room temperature for 10 min, 1.2 mmol of epoxy chloropropane is added, heated to 60 DEG C for reaction for 2 h, rotary evaporation is performed at 60 DEG C, excess ethyl acetate is added into the crude product, frozen recrystallization is performed, the supernatant is removed, ethyl acetate is added again, the above-mentioned frozen recrystallization is repeated for 3 times, and the supernatant is removed to obtain a quaternary ammonium salt intermediate; S4: 9 g of carboxymethyl cellulose sodium is ultrasonically dispersed in N,N-dimethylformamide, 0.01 mol / L of sodium hydroxide solution is added, stirred for 10 min, 1.6 g of the quaternary ammonium salt intermediate is added, heated to 80 DEG C for reaction for 5 h, cooled to room temperature, the upper solvent is removed, excess ethyl acetate is added, stirred, placed, the upper clear liquid is removed, the above-mentioned operation of adding ethyl acetate, stirring, and placing is repeated for 3 times, and rotary evaporation is performed to obtain quaternary ammonium salt carboxymethyl cellulose sodium; S5: 4 g of the quaternary ammonium salt carboxymethyl cellulose sodium and 1 g of boron nitride nanosheet are added into a ball mill tank, ball milled for 10 h under nitrogen atmosphere, ultrasonically dispersed in deionized water, centrifuged, and vacuum dried to obtain quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet; S6: 100 g of chlorinated polyethylene powder, 12 g of quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet, 4 g of heat stabilizer, 2 g of p-phenylenediamine, and 4 g of terephthalyl chloride were added to a mixer, heated to 80 DEG C, and stirred for 45 min to obtain a premix; S7: 100 g of the premix was added to a twin-screw extruder, 0.3 g of calcium stearate was added, melt blended, extruded, vacuum shaped at room temperature, and cooled and shaped to obtain a high-temperature-resistant and low-permeability CPVC chemical pipe.
[0020] Example 2: A preparation process of a high-temperature-resistant and low-permeability CPVC chemical pipe, comprising the following steps: S1: 1.35 g of adenine, 0.5 g of potassium hydroxide, and 100 mL of ionized water were added, heated to 100 DEG C, stirred until uniform, 1.84 g of anhydrous zinc acetate was added, and the mixture was incubated for 2 h, cooled, filtered, the precipitate was washed, vacuum dried, ground, and an adenine metal complex was obtained; S2: 4 g of the adenine metal complex and 2 g of theophylline were compounded to obtain a heat stabilizer; S3: 1 mmol of oleamide propyl dimethylamine, 0.01 mmol of concentrated hydrochloric acid, and 50 mL of ethanol were added to a reaction container, stirred at room temperature for 10 min, 1.2 mmol of epichlorohydrin was added, heated to 60 DEG C, and reacted for 2 h, 60 DEG C rotary evaporation, excess ethyl acetate was added to the crude product, frozen and recrystallized, the supernatant was removed, ethyl acetate was added again, and the above-mentioned frozen recrystallization was repeated 3 times to obtain a quaternary ammonium salt intermediate; S4: 9 g of carboxymethyl cellulose sodium was ultrasonically dispersed in N,N-dimethylformamide, 0.01 mol / L of sodium hydroxide solution was added, stirred for 10 min, 1.6 g of the quaternary ammonium salt intermediate was added, heated to 80 DEG C, and reacted for 5 h, cooled to room temperature, the upper solvent was removed, excess ethyl acetate was added, stirred, and the supernatant was removed after standing, the above-mentioned operation of adding ethyl acetate, stirring, and standing was repeated 3 times, and rotary evaporation was performed to obtain quaternary ammonium salt carboxymethyl cellulose sodium; S5: 4 g of quaternary ammonium salt carboxymethyl cellulose sodium and 1 g of boron nitride nanosheet were added to a ball mill tank, ball milled for 10 h under a nitrogen atmosphere, ultrasonically dispersed in deionized water, centrifuged, and vacuum dried to obtain quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet; S6: 100 g of chlorinated polyethylene powder, 16 g of quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet, 5 g of heat stabilizer, 3 g of p-phenylenediamine, and 6 g of terephthalyl chloride were added to a mixer, heated to 80 DEG C, and stirred for 45 min to obtain a premix; S7: 100 g of the premix was added to a twin-screw extruder, 0.3 g of calcium stearate was added, melt blended, extruded, vacuum shaped at room temperature, and cooled and shaped to obtain a high-temperature-resistant and low-permeability CPVC chemical pipe.
[0021] Example 3: A preparation process for high temperature resistant and low permeability CPVC chemical pipe, comprising the following steps: S1: 1.35g adenine and 0.5g potassium hydroxide are added to 100mL of deionized water, heated to 100℃ and stirred evenly, 1.84g anhydrous zinc acetate is added, the reaction is kept at the temperature for 2h, cooled, filtered, the precipitate is washed, vacuum dried, and ground to obtain adenine metal complex; S2: Combine 4g of adenine metal complex with 2g of theophylline to obtain a heat stabilizer; S3: Add 1 mmol of oleamidopropyl dimethylamine, 0.01 mmol of concentrated hydrochloric acid, and 50 mL of ethanol to a reaction vessel, stir at room temperature for 10 min, add 1.2 mmol of epichlorohydrin, heat to 60 °C and react for 2 h, rotary evaporate at 60 °C, add excess ethyl acetate to the crude product, freeze recrystallize, remove the supernatant, add ethyl acetate again, repeat the above freeze recrystallization and supernatant removal operation 3 times to obtain the quaternary ammonium salt intermediate; S4: 9g of sodium carboxymethyl cellulose was ultrasonically dispersed in N,N-dimethylformamide, 0.01mol / L sodium hydroxide solution was added, and the mixture was stirred for 10min. 1.6g of quaternary ammonium salt intermediate was added, and the mixture was heated to 80℃ and reacted for 5h. After cooling to room temperature, the upper solvent was removed, excess ethyl acetate was added, the mixture was stirred, allowed to stand, and the upper clear liquid was removed. The above process of adding ethyl acetate, stirring, and allowing to stand, and removing the upper clear liquid was repeated 3 times. The mixture was then rotary evaporated to obtain sodium carboxymethyl cellulose quaternary ammonium salt. S5: Add 4g of sodium carboxymethyl cellulose quaternary salt and 1g of boron nitride nanosheets to a ball milling jar, ball mill for 10h under nitrogen atmosphere, add deionized water, ultrasonically disperse, centrifuge, and vacuum dry to obtain sodium carboxymethyl cellulose quaternary salt modified boron nitride nanosheets. S6: 100g of chlorinated polyethylene powder, 20g of sodium carboxymethyl cellulose quaternary ammonium salt modified boron nitride nanosheets, 6g of heat stabilizer, 4g of p-phenylenediamine, and 8g of terephthaloyl chloride are added to a mixer, heated to 80℃, and stirred for 45min to obtain a premix. S7: Add 100g of premix to a twin-screw extruder, add 0.3g of calcium stearate, melt blend, extrude, vacuum set at room temperature, and cool to set to obtain high-temperature resistant, low-permeability CPVC chemical pipe.
[0022] Comparative Example 1: A preparation process for a high-temperature resistant and low-permeability CPVC chemical pipe, comprising the following steps: S1: 1.35g adenine and 0.5g potassium hydroxide are added to 100mL of deionized water, heated to 100℃ and stirred evenly, 1.84g anhydrous zinc acetate is added, the reaction is kept at the temperature for 2h, cooled, filtered, the precipitate is washed, vacuum dried, and ground to obtain an adenine metal complex heat stabilizer; S2: 1 mmol of oleamide propyl dimethylamine, 0.01 mmol of concentrated hydrochloric acid, 50 mL of ethanol were added to the reaction container, stirred at room temperature for 10 min, 1.2 mmol of epichlorohydrin was added, heated to 60°C for 2h, 60°C rotary evaporation, excess ethyl acetate was added to the crude product, freeze recrystallization, remove supernatant, add ethyl acetate again, repeat the above freeze recrystallization, remove supernatant operation 3 times, to obtain the quaternary ammonium salt intermediate; S3: 9g carboxymethyl cellulose sodium was ultrasonically dispersed in N,N- dimethylformamide, 0.01mol / L sodium hydroxide solution was added, stirred for 10 min, 1.6g quaternary ammonium salt intermediate was added, heated to 80°C for 5h, cooled to room temperature, remove the upper solvent, add excess ethyl acetate, stir, stand, remove the supernatant, repeat the above operation of adding ethyl acetate, stirring, standing, removing the supernatant 3 times, rotary evaporation, to obtain quaternary ammonium salt carboxymethyl cellulose sodium; S4: 4g quaternary ammonium salt carboxymethyl cellulose sodium, 1g boron nitride nanosheet was added to the ball mill tank, under nitrogen atmosphere, ball milling for 10h, added deionized water, ultrasonic dispersion, centrifugation, vacuum drying, to obtain quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet; S5: 100g chlorinated polyethylene powder, 12g quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet, 4g heat stabilizer, 2g p- phenylenediamine, 4g terephthaloyl chloride were added to the mixer, heated to 80°C, stirred for 45min, to obtain the premix; S6: 100g premix was added to the twin screw extruder, 0.3g calcium stearate was added, melt blending, extrusion molding, vacuum setting at room temperature, cooling setting, to obtain high temperature resistant low permeability CPVC chemical pipe.
[0023] Comparative example 2: a preparation process of a high temperature resistant low permeability CPVC chemical pipe, comprising the following steps: S1: 1.35g adenine, 0.5g potassium hydroxide was added to 100mL ionized water, heated to 100°C and stirred uniformly, 1.84g anhydrous zinc acetate was added, incubated for 2h, cooled, filtered, washed the precipitate, vacuum dried, ground, to obtain adenine metal complex; S2: 4g adenine metal complex and 2g theophylline were compounded to obtain a heat stabilizer; S3: 4g carboxymethyl cellulose sodium, 1g boron nitride nanosheet was added to the ball mill tank, under nitrogen atmosphere, ball milling for 10h, added deionized water, ultrasonic dispersion, centrifugation, vacuum drying, to obtain carboxymethyl cellulose sodium modified boron nitride nanosheet; S4: 100g chlorinated polyethylene powder, 12g quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet, 4g heat stabilizer, 2g p- phenylenediamine, 4g terephthaloyl chloride were added to the mixer, heated to 80°C, stirred for 45min, to obtain the premix; S5: 100 g of the premix was added to a twin-screw extruder, 0.3 g of calcium stearate was added, melt blended, extruded, vacuum shaped at room temperature, and cooled and shaped to obtain a high-temperature-resistant and low-permeability CPVC chemical pipe.
[0024] Comparative Example 3: A preparation process of a high-temperature-resistant and low-permeability CPVC chemical pipe, comprising the following steps: S1: 1.35 g of adenine, 0.5 g of potassium hydroxide was added to 100 mL of ionized water, heated to 100℃ and stirred uniformly, 1.84 g of anhydrous zinc acetate was added, and reacted for 2 h, cooled, filtered, washed the precipitate, vacuum dried, and ground to obtain an adenine metal complex; S2: 4 g of the adenine metal complex and 2 g of theophylline were compounded to obtain a thermal stabilizer; S3: 1 mmol of oleamide propyl dimethylamine, 0.01 mmol of concentrated hydrochloric acid, and 50 mL of ethanol were added to a reaction container, stirred at room temperature for 10 min, 1.2 mmol of epichlorohydrin was added, heated to 60℃ and reacted for 2 h, 60℃ rotary evaporation, excess ethyl acetate was added to the crude product, freeze recrystallization, remove the supernatant, add ethyl acetate again, repeat the above freeze recrystallization, remove the supernatant 3 times to obtain a quaternary ammonium salt intermediate; S4: 9 g of carboxymethyl cellulose sodium was ultrasonically dispersed in N,N-dimethylformamide, 0.01 mol / L sodium hydroxide solution was added, stirred for 10 min, 1.6 g of the quaternary ammonium salt intermediate was added, heated to 80℃ and reacted for 5 h, cooled to room temperature, removed the upper solvent, added excess ethyl acetate, stirred, stood, removed the upper clear liquid, repeated the above operation of adding ethyl acetate, stirring, standing, and removing the upper clear liquid 3 times, rotary evaporation to obtain a quaternary ammonium salt carboxymethyl cellulose sodium; S5: 4 g of the quaternary ammonium salt carboxymethyl cellulose sodium, 1 g of boron nitride nanosheet were added to a ball mill tank, ball milled for 10 h under nitrogen atmosphere, ultrasonically dispersed in deionized water, centrifuged, and vacuum dried to obtain a quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet; S6: 100 g of chlorinated polyethylene powder, 12 g of the quaternary ammonium salt carboxymethyl cellulose sodium modified boron nitride nanosheet, and 4 g of the thermal stabilizer were added to a mixer, heated to 80℃, and stirred for 45 min to obtain a premix; S7: 100 g of the premix was added to a twin-screw extruder, 0.3 g of calcium stearate was added, melt blended, extruded, vacuum shaped at room temperature, and cooled and shaped to obtain a high-temperature-resistant and low-permeability CPVC chemical pipe.
[0025] Test: Hydrostatic strength test: the test temperature was 95℃, the test time was 165 h, and the hydrostatic stress was 5.6 MPa; Vicat softening temperature test: tested according to ASTM D1525; Longitudinal shrinkage test: test according to GB / T 6671-2001, test temperature 150°C; The experimental data are shown in Table 1 below.
[0026] Table 1 Test data table of high-temperature-resistant and low-permeability CPVC chemical pipe
[0027] Conclusion: Example 1 single heat stabilizer, lack of theophylline and adenine metal complex coordination effect, wrapped reaction generated ZnCl2, easy to appear traditional zinc-based stabilizer "zinc burn" problem.
[0028] Example 2 carboxymethyl cellulose sodium modified boron nitride nanosheet, lack of surface oleic acid C=C bond further adsorption CPVC high temperature degradation of HCl in acidic environment, from the source to inhibit CPVC due to HCl catalytic caused "zipper type degradation".
[0029] Example 3 lack of p-phenylenediamine, terephthaloyl chloride, lack of in-situ polymerization to generate aramid nanomaterials, can not fill the microvoids in CPVC matrix, resulting in an increase in the medium penetration channel.
[0030] It should be apparent to those skilled in the art that the application is not limited to the details of the foregoing exemplary embodiments, and that the present application can be carried out in other embodiments that do not depart from the spirit or essential characteristics of the application. The present embodiments are, therefore, to be considered in all respects as illustrative and not restrictive, and all changes coming within the meaning and equivalency range of the appended claims are intended to be embraced therein.
Claims
1. A preparation process of high-temperature-resistant and low-permeability CPVC chemical pipe material, characterized in that: The method comprises the following steps: S1: chlorinated polyethylene powder, quaternary ammonium salt sodium carboxymethyl cellulose modified boron nitride nanosheet, heat stabilizer, p-phenylenediamine, terephthalyl chloride are added into a mixing machine, heated to 80-90 DEG C, stirred for 45-60 min to obtain a premix; S2: the premix is added into a double screw extruder, calcium stearate is added, melt blending is performed, extrusion molding is performed, vacuum shaping is performed at room temperature, and cooling shaping is performed to obtain the high-temperature-resistant and low-permeability CPVC chemical pipe; The heat stabilizer is composed of adenine metal complex and theophylline.
2. The preparation process of high-temperature-resistant and low-permeability CPVC chemical pipe according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt sodium carboxymethyl cellulose modified boron nitride nanosheet comprises the following steps: step (1): oleamide propyl dimethylamine, concentrated hydrochloric acid and ethanol are added into a reaction container, stirred at room temperature for 10-15 min, epichlorohydrin is added, heated to 60-65 DEG C and reacted for 2-2.5 h, 60-62 DEG C is rotated and evaporated, purified to obtain a quaternary ammonium salt intermediate; Step (2): sodium carboxymethyl cellulose is ultrasonically dispersed in N,N-dimethylformamide, sodium hydroxide solution is added, stirred for 10-15 min, the quaternary ammonium salt intermediate is added, heated to 80-85 DEG C and reacted for 5-5.5 h, purified, and evaporated under reduced pressure to obtain the quaternary ammonium salt sodium carboxymethyl cellulose; Step (3): the quaternary ammonium salt sodium carboxymethyl cellulose and boron nitride nanosheet are added into a ball mill tank, ball milled for 10-12 h under a nitrogen atmosphere, ultrasonically dispersed in deionized water, centrifuged, and vacuum dried to obtain the quaternary ammonium salt sodium carboxymethyl cellulose modified boron nitride nanosheet.
3. The process for preparing high temperature resistant and low permeability CPVC chemical pipe according to claim 2, characterized in that: In the preparation process of the quaternary ammonium salt intermediate, the molar ratio of oleamide propyl dimethylamine to epichlorohydrin is 1:(1-1.5).
4. The process for preparing high temperature resistant and low permeability CPVC chemical pipe according to claim 2, characterized in that: In the preparation process of the quaternary ammonium salt sodium carboxymethyl cellulose, the mass ratio of sodium carboxymethyl cellulose to the quaternary ammonium salt intermediate is 9:(1.6-2.0).
5. The process for preparing high temperature resistant and low permeability CPVC chemical pipe according to claim 2, characterized in that: In the preparation process of the quaternary ammonium salt sodium carboxymethyl cellulose modified boron nitride nanosheet, the mass ratio of the quaternary ammonium salt sodium carboxymethyl cellulose to the boron nitride nanosheet is (4-5):
1.
6. The process for preparing high temperature resistant and low permeability CPVC chemical pipe according to claim 1, characterized in that: In the heat stabilizer, the mass ratio of adenine metal complex to theophylline is (2-3):(1-1.5).
7. The process for preparing high temperature resistant and low permeability CPVC chemical pipe according to claim 1, characterized in that: The preparation process of the adenine metal complex comprises the following steps: adenine and potassium hydroxide are added into deionized water, heated to 100-105 DEG C and stirred uniformly, anhydrous zinc acetate is added, incubated and reacted for 2-2.5 h, cooled, filtered, washed the precipitate, vacuum dried, ground to obtain the adenine metal complex.
8. The process for preparing high temperature resistant and low permeability CPVC chemical pipe according to claim 7, characterized in that: In the preparation process of the adenine metal complex, the mass ratio of adenine to potassium hydroxide to anhydrous zinc acetate is (1.35-1.5):(0.5-0.52):(1.84-1.96).
9. The process for preparing high temperature resistant low permeability CPVC chemical pipe according to claim 1, characterized in that: In the premix, the proportions of the components include, by mass fraction: 90-100 parts of chlorinated polyethylene powder, 12-20 parts of quaternary ammonium salt sodium carboxymethyl cellulose modified boron nitride nanosheet, 4-6 parts of heat stabilizer, 2-4 parts of p-phenylenediamine, and 4-8 parts of terephthalyl chloride; in the preparation process of the high-temperature-resistant and low-permeability CPVC chemical pipe, the amount of calcium stearate added is 0.2-0.5% of the mass of the premix.
10. The high-temperature-resistant and low-permeability CPVC chemical pipe prepared by the preparation process according to claim 1.
Citation Information
Patent Citations
Carbon nanotube / boron nitride composite modified CPVC pipe with high heat conductivity and preparation method
CN107189292A
Adenine metal complex as well as preparation method and application thereof
CN113265066A
Cited By
Guanine PVC heat stabilizer and application thereof
CN121975185A